Use of drug in the form of spray based on Flumethrin, Moxidectin and Pyriproxyfen against entomosis in small domestic animals - S. B. Devyatyarova (Российский паразитологический журнал, 2024)
The purpose of the research is to study the efficacy of a Flumethrin-, Moxidectin and Pyriproxyfen-based spray against entomosis in dogs and cats.Materials and methods. The therapeutic efficacy of the multicomponent spray against entomosis of cats and dogs was evaluated in the Podolsk Experimental Production Base of the VNIIP – FSC VIEV on 100 animals naturally infected with fleas Ctenocephalides spp. (20 cats and 20 dogs), Linognathus setosus (20 dogs), chewing lice Felicola subrostratus (20 cats) and Trichodectes canis (20 dogs). The animals were divided into experimental and control groups of 10 animals each. The experimental dogs and cats were given the drug topically with a bottle pump directed to the skin and fur from 20–25 cm, treating the entire body of the animal at a dose of 3–6 pumps per 1 kg of animal weight, and the control animals were not given the drug. The animals were observed for 60 days after a single dose of the drug; clinical examination was performed before and at 24, 48 hours and 5, 30 and 60 days after the start of the experiment.Results and discussion. The examination of the skin and coat of some experimental animals infected with ectoparasites found single ectoparasite imago at 24 hours after treatment. At 48 hours and on day 5, 30 and 60 of the experiment, all animals treated once with the drug were free from ectoparasites, which was evidenced by clinical studies. The study results showed that the study drug had high therapeutic efficacy against ctenocephalidosis, linognathosis, and trichodectosis in dogs and cats.